3S1–3D1 coupled channel ΛcN interactions: chiral effective field theory versus lattice QCD. (1st January 2023) - Song, Jing; Xiao, Yang; Liu, Zhi-Wei; Li, Kai-Wen; Geng, Li-Sheng
Abstract: We study the lattice QCD Λ c N phase shifts for the 3 S 1 – 3 D 1 coupled channel using both the leading order covariant chiral effective theory and the next-to-leading order non-relativistic chiral effective field theory (ChEFT). We show that although it is possible to describe simultaneously the 3 S 1 and 3 D 1 phase shifts and the inelasticity η 1, the fitted energy range is quite small, only up to E c.m. = 5 MeV. This raises concerns regarding the consistency between leading/next-to-leading order ChEFT and the lattice QCD simulations.